2021
DOI: 10.1002/jcp.30289
|View full text |Cite
|
Sign up to set email alerts
|

GDF‐15: Diagnostic, prognostic, and therapeutic significance in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the commonest primary malignant brain tumor and has a remarkably weak prognosis. According to the aggressive form of GBM, understanding the accurate molecular mechanism associated with GBM pathogenesis is essential. Growth differentiation factor 15 (GDF‐15) belongs to transforming growth factor‐β superfamily with important roles to control biological processes. It affects cancer growth and progression, drug resistance, and metastasis. It also can promote stemness in many cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…Studies have shown that RAB42 can promote the proliferation, migration and invasion of glioma cells [ 43 , 44 ]. And in addition to these functions, GDF15 can regulate immune infiltration of glioma and promote stem cell-like phenotype [ 45 , 46 ]. However, the role of SH2D4A in glioma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that RAB42 can promote the proliferation, migration and invasion of glioma cells [ 43 , 44 ]. And in addition to these functions, GDF15 can regulate immune infiltration of glioma and promote stem cell-like phenotype [ 45 , 46 ]. However, the role of SH2D4A in glioma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…35,48 On the other hand, GDF-15 regulates the tumor microenvironment and promotes the proliferation, angiogenesis, and metastasis of tumor cells in the progression of cancers, such as breast cancer, stomach cancer, and colorectal cancer. 40,[49][50][51][52] In addition, studies suggest that GDF-15 increases rapidly with the occurrence of myocardial ischemia or reperfusion injury to reduce myocardial injury, inhibit inflammatory mediators such as TNF-α and IL-1β, and combat atherosclerosis and myocardial infarction. 53,54 GDF-15 regulates smooth muscle cells and inhibits vascular remodeling to maintain vascular health, especially in hypertensive diseases.…”
Section: The Structure and Functions Of Gdf-15mentioning
confidence: 99%
“…Glioblastoma multiforme (GB), also known as WHO‐grade IV glioma, is the most prevalent and lethal primary malignant tumor of the central nervous system (CNS), with a dismal prognosis despite substantial breakthroughs in disease treatment and the introduction of multimodal strategies combining surgery and chemoradiation ( 1 3 ). The limited efficacy of current therapeutic schemes is a cause of concern in the therapy of patients.…”
Section: Introductionmentioning
confidence: 99%